Successful treatment of lichen amyloidosis accompanied by atopic dermatitis by fractional CO2 laser. (18th August 2017) - Chu, Howard; Shin, Jung U.; Lee, Jungsoo; Park, Chang Ook; Lee, Kwang Hoon
ABSTRACT: Lichen amyloidosis (LA) is a subtype of primary cutaneous amyloidosis that is presented as persistent, multiple-grouped hyperkeratotic papules usually located on the shins, back, forearms or thighs. The treatment of LA has been considered to be difficult, and of the various methods available, recent studies have reported the efficacy of fractional CO2 lasers. LA may be accompanied by atopic dermatitis (AD) in which the treatment options may be more limited. Herein, we report three cases of LA accompanied by AD treated by a fractional CO2 laser.